Self-transcendence: an alternative explanation for voluntourism in developing countries - Tukamushaba, Eddy K.; Xiao, Honggen; Ladkin, Adele (International Journal of Sustainable Society, 2017)
Travel associated with volunteering activities has been on increase and has attracted a cross section of people with varying demographic characteristics. This paper argues for self-transcendence as an alternative altruistic motivation for VOLUNtourists to travel to developing countries. A descriptive research design was used to guide the research process. A sample of 501 respondents who had completed their visit to Uganda for various reasons was used. Results indicate that, there was no significant association between gender and purpose of the visit, while age group was significantly associated with the purpose of visiting. Most visitors were seeking what was perceived to be at a being level. In Uganda most facilities within tourist attractions favour the adult age group and it is recommended that special consideration be put towards the development of affordable accommodation to cater for all age groups.
Keywords: VOLUNtourism; travel motivation; self-transcendence